2016
DOI: 10.1039/c5ra27922d
|View full text |Cite
|
Sign up to set email alerts
|

Li-doped graphene for spintronic applications

Abstract: Generating spintronic devices has been a goal for nanoscience. Here, Li-doped graphene flakes are proposed for spintronic applications. To achieve this goal, density functional theory has been used to determine the magnetic phases of monolayer and bilayer doped graphene nanoflakes. The adsorption energies, spin polarizations, electronic gaps, magnetic properties and robustness of spin-polarized states have been studied in the presence of dopants and second layers. Based on these results, graphene flakes have b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Besides, by the increase of the size, the HOMO state has a redshift, and the LUMO state has a blueshift (figure 4) to decrease the gap. Before, it has been shown that the absorption of a Li atom makes a graphene flake to be spin-polarized [47,50,51]. In this work, we have also spin polarization of frontier MOs of Li-doped flakes.…”
Section: Dos Homo-lumo Gap and Frontier Molecular Orbitalsmentioning
confidence: 72%
“…Besides, by the increase of the size, the HOMO state has a redshift, and the LUMO state has a blueshift (figure 4) to decrease the gap. Before, it has been shown that the absorption of a Li atom makes a graphene flake to be spin-polarized [47,50,51]. In this work, we have also spin polarization of frontier MOs of Li-doped flakes.…”
Section: Dos Homo-lumo Gap and Frontier Molecular Orbitalsmentioning
confidence: 72%
“…Before, it has been shown that the absorption of a Li atom makes a graphene flake to be spin-polarized [42,45,46]. In this work, we have also spin polarization of frontier MOs of Li-doped flakes.…”
Section: Dos Homo-lumo Gap and Frontier Molecular Orbitalsmentioning
confidence: 72%